Implementation of Strategic Management Based on Finger Print Technology for Improving the Teachers Work Ethics - Erwin Muslimin (UIN Sunan Gunung Djati Bandung, 2016)
This article discusses strategic management at the school for educators. Strategic management of the school for educators is to support the development and construction of an educational institution for excellence and quality. If in the modern era which are all based on technology, computers, applications and the Internet, it is very unfortunate if there is an educational institution that still apply strategic management within the school administrative data processing by hand. It will not be effective and will take a very long time. With the application of finger print-based strategic management to monitor it all, it will facilitate an educational institution in managing data administration required, especially to see the work ethic of an educator as seen from the attendance list presence. This study aims to determine the extent to which management implementations finger print-based strategies to improve work ethics of teachers in the State Madrasah Aliyah (MAN) 1 Bandung. The research was conducted by interview or observation related technologies, applications, and data administration for educators in the State Madrasah Aliyah (MAN) 1 Bandung. With the finger print-based strategic management, it will be easier for the school to monitor and assess the work ethic of existing educators in the school.